ROLE OF TAX INCENTIVES IN PROMOTING ENTREPRENEURIAL DEVELOPMENT: A STUDY OF SMES IN LAGOS, NIGERIA - Oluwaseyi Ayodele ADEDIPE (Malete Journal of Accounting and Finance, 2025)
Small and Medium Enterprises (SMEs) are widely recognized as critical drivers of economic development, employment generation, and innovation in Nigeria. However, in Lagos State, SMEs continue to face numerous challenges, including high tax burdens and limited government support, which hinder entrepreneurial growth and sustainability. This study investigated the role of tax incentives in promoting entrepreneurial development among small and medium-sized enterprises (SMEs) in Lagos, Nigeria. Using a sample of 150 respondents, the study examined the effects of three major tax incentive components tax holidays, tax deductions, and capital allowances—on the start-up, growth, and sustainability of SMEs. Data were collected through structured questionnaires and analyzed using simple linear regression and analysis of variance (ANOVA). The findings revealed that tax holidays significantly influenced the early growth of SMEs, tax deductions enhanced their operational performance and reinvestment capacity, while capital allowances positively impacted long-term expansion and sustainability. These results underscore the importance of a well-structured tax incentive framework in supporting entrepreneurial activities. The study concluded that effective and accessible tax incentives play a crucial role in fostering SME development and recommended the expansion, simplification, and strategic implementation of tax relief policies to stimulate entrepreneurship and drive inclusive economic growth in Nigeria.